2002
DOI: 10.1093/carcin/23.2.317
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the isoflavone 4′,5,7-trihydroxyisoflavone (genistein) on psoralen plus ultraviolet A radiation (PUVA)-induced photodamage

Abstract: Long-term psoralen plus ultraviolet A radiation (PUVA) therapy is associated with an increased risk of squamous cell carcinoma and malignant melanoma. Genistein (4',5,7-trihydroxyisoflavone), a major isoflavone in soybeans and a specific inhibitor of protein tyrosine kinase, has been shown to inhibit UVB induced skin carcinogenesis in hairless mice. For this study we examined the protective effects of topical genistein on PUVA-induced photodamage. In two separate experiments, genistein in a dimethyl sulfoxide/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 30 publications
2
39
0
Order By: Relevance
“…24 Moreover, the isoflavone genistein, a specific inhibitor of tyrosine kinase, has been shown to inhibit chemical carcinogeninduced reactive oxygen species and PUVA-induced photodamage, including inflammatory skin changes such as dermal neutrophilic and lymphocytic infiltration. 25 We observed that ex vivo PUVA-treated and UVAtreated PC but not unirradiated PC induced immune suppression in a dose-dependent manner (Figure 1c). Surprisingly however, there was no difference in the UVA dose response dependency or the UVA threshold dose for immune suppression, irrespective whether or not psoralen was added to the UVA-irradiated PC solution before UVA irradiation.…”
Section: Discussionmentioning
confidence: 80%
“…24 Moreover, the isoflavone genistein, a specific inhibitor of tyrosine kinase, has been shown to inhibit chemical carcinogeninduced reactive oxygen species and PUVA-induced photodamage, including inflammatory skin changes such as dermal neutrophilic and lymphocytic infiltration. 25 We observed that ex vivo PUVA-treated and UVAtreated PC but not unirradiated PC induced immune suppression in a dose-dependent manner (Figure 1c). Surprisingly however, there was no difference in the UVA dose response dependency or the UVA threshold dose for immune suppression, irrespective whether or not psoralen was added to the UVA-irradiated PC solution before UVA irradiation.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, it has been reported that the inhibition of PARP-1 activity is a promising strategy to improve the outcome of cytotoxic therapies in different tumor models [17].…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies indicate that the SERMs tamoxifen, raloxifene and genistein all substantially benefit healing in the estrogen-deprived Ovx mouse, promoting re-epithelialisation and contraction, and reducing inflammation, an effect that is most likely mediated via ERb (Emmerson et al 2010;Hardman et al 2008), while a separate study provides evidence that genistein accelerates murine healing by modulating TGFb1 (Marini et al 2010). Tamoxifen, raloxifene and genistein are anti-inflammatory in other pathologies, including systemic lupus erythematosus (SLE) (Sthoeger et al 2003), stroke (Tian et al 2009), UV-associated cutaneous damage (Brand and Jendrzejewski 2008;Shyong et al 2002;Widyarini et al 2001), colitis (Seibel et al 2009), ileitis (Sadowska-Krowicka et al 1998) and multiple sclerosis (MS) (De Paula et al 2008). An important and on-going goal of our research is to evaluate cutaneous healing in post-menopausal women prescribed topical SERM treatment.…”
Section: Estrogen Receptors and Sermsmentioning
confidence: 99%